METHODICAL APPROACHES TO THE MANAGEMENT PROCESS IN PUBLIC AUTHORITIES ON THE BASIS OF OUTSOURCING - Kalinin, Maksym (Pressing Problems of Public Administration, 2021)
The article attempts to determine the methodological principles of using outsourcing in public authorities. The correlation of outsourcing with the concepts of cooperation, contracting, privatization, public procurement, public-private partnership, etc. is determined. The ideas about the essence of outsourcing are systematized. The signs of outsourcing in public authorities are revealed, including: delegation (transferring) of activities (performance of works, provision of services) to third-party organizations; development of common principles for taking certain types of activities out of the functioning (including those behind the physical boundaries) of public authorities; the system of economic relations and actions that arise when involving external contractors to perform certain activities; the contractual nature of the relationship arising from outsourcing; competitive basis for determining external contractors; maintaining responsibility and control in the public authority over the results of the type of activity outsourced. A model of a pyramid of outsourcing initiatives in public authorities has been developed, which includes the following hierarchies by levels: – one-time outsourcing, i.e. individual interactions of public authorities and external organizations to solve certain tasks and perform certain operations; – resource outsourcing or infrastructure outsourcing (infrastructure services), which involves the acquisition of certain resources or services to support the activities of a public authority (for example, software products, communication services, human resources for PR campaigns or social events); – transfer of execution of a certain management process or its part to the external organization aiming to increase their qualitative characteristics, efficiency and reduction of expenses for its realization. Outsourcing of management processes differs from the next level because the subject of outsourcing in this case is not a function as a whole, but a set of management processes performed in the implementing one or more functions. It is not the solution of a single task or the execution of a single operation that is outsourced, but the provision of the entire management process. The third-party organization undertakes the work of implementing the management process, and is also responsible for ensuring that this process is consistent with other processes in the organization and the output would give the expected results. – outsourcing of functions, within which the whole set of management processes (within one or more public functions) is transferred to the external organization. – transformational outsourcing is a radical change, complete reorganization and rethinking of management processes of public authorities on the basis of outsourcing. It is noted that outsourcing in public authorities is also classified by the nature of the activities outsourced (personnel outsourcing, information technology outsourcing, etc.), depending on the amount of outsourced work (full outsourcing and partial outsourcing). The current trends in the use of outsourcing in the public sector of Ukraine and foreign countries are defined. They include the following: – first, the transition from one-time outsourcing of individual operations to outsourcing of management processes and large-scale process of transformation of outsourcing; – secondly, the changes of the reasons to address the outsourcing (from the need to reduce costs to the need to transform activities) in order to improve the efficiency of management processes; – third, the focus of government officials on tasks related to the management of contractual relations; – fourth, the establishment of partnerships between public authorities and external contractors on the basis of long-term agreements; – fifth, the change in the content of contracts, the formation of a special type of law governing contractual relations between public authorities and external organizations; – sixth, the formation of an institutional framework for contract management.